STUDI TENTANG PENGGUNAAN BAHAN AJAR MATA PELAJARAN EKONOMI MATERI AKUNTANSI KELAS XI IPS DI SMA NEGERI 1 KRIAN - TRI YOGI SETIYARINI (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2013)
Education is the most important thing in a country to become better in future. The quality of the education can be measured by the succeed of the teaching and learning processes. There are three aims of this research. First, to find out the learning materials that is used by the teacher to teach accounting for social eleventh graders. Second, the reason of the teacher using the learning materials. Third, to find out the feasibility of the learning materials that is used by the teacher in teaching accounting for XI social graders in SMA Negeri 1 Krian. This research was descriptive. The data was collected by using interview and checklist. The result of the study was the teaching and learning process in SMA Negeri 1 Krian used BSE Ekonomi and Module Economic Accounting. BSE Ekonomi had 90,23% with very good feasibility and Module Economic Accounting had 79,15% with very good feasibility. So that the researcher concluded that BSE Ekonomi and Module Economic Accounting were suitable to teach accounting because they suits the BSNP reference. Keywords: Learning Materials, Feasibility, BSNP